Functional peptides from yellowfin tuna (Thunnus albacares): Characterisation and storage stability assessment - Parvathy, U.; Binsi, P. K.; Visnuvinayagam, S.; Zynudheen, A. A.; Ninan, George; Ravishankar, C. N. (Indian Journal of Fisheries, 2020)
Present study attempted the effective utilisation of tuna red meat which is a major cannery waste from tuna industry, by recovery in the form of bioactive peptides. Protein hydrolysate from yellowfin tuna red meat was, characterised for functional properties. Molecular weight profile of the derived hydrolysate revealed its heterogeneity in peptide pattern with a major distribution above 10 kDa (60%). A protein recovery of 39.64% was obtained from the raw material with a protein content of 88.57Â±0.66% in the derived tuna protein hydrolysate (TPH). Present study revealed TPH to have rich levels of amino acids like glutamic acid, aspartic acid, lysine and leucine while phenyl alanine, tyrosine, methionine and cysteine were found in lower amounts. Variations in foaming properties at different pH levels ranging from 2-10 indicated these properties to be maximum at pH 6.0. Similarly, emulsion stability index was highest (48.09Â±2.69 min) at pH of 6.0. However, emulsifying activity index increased with increase in pH. The storage stability studies carried out for TPH at ambient (28oC) and chilled storage conditions (4oC) for upto six months indicated an uptake of moisture, increase in oxidative indices as well as changes in functionality which was more prominent under ambient conditions. Results suggested protein hydrolysate from tuna red meat to be a promising source of bioactive peptides, finding suitability in formulation of functional foods as well as nutraceutical products.Keywords: Functional properties, Papain, Storage stability, Tuna protein hydrolysate, Yellowfin tunaÂ